2004
DOI: 10.1262/jrd.50.627
|View full text |Cite
|
Sign up to set email alerts
|

Production of Offspring from One-Day-Old Oocytes Stored at Room Temperature

Abstract: Abstract.To determine the feasibility of preserving oocytes without freezing, we stored mouse oocytes in several media at different temperatures for one day. Confocal microscopy of the metaphase-II spindle in these stored oocytes revealed gross abnormalities in both the spindle and the arrangement of chromosomes. The abnormal spindles could not be rescued by transplanting the aged spindle-chromosome complex into a fresh enucleated oocyte. A diploid parthenogenetic development showed that some of the oocytes st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 39 publications
3
62
1
1
Order By: Relevance
“…As reported here, ntES cell lines can be easily established in an outbred (ICR) strain from which cloned mice were first obtained by second nuclear transfer. Because even ntES cells from inbred cloned blastocysts are able to multiply indefinitely in vitro (28) like ordinary ES cells, we should be able to maintain abnormal Y chromosomes in the ntES cell lines or in live animals by using the tetraploid complementation method. We believe that, as cloning techniques continue to improve, we will be able to maintain any infertile lines of both males and females by using their somatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported here, ntES cell lines can be easily established in an outbred (ICR) strain from which cloned mice were first obtained by second nuclear transfer. Because even ntES cells from inbred cloned blastocysts are able to multiply indefinitely in vitro (28) like ordinary ES cells, we should be able to maintain abnormal Y chromosomes in the ntES cell lines or in live animals by using the tetraploid complementation method. We believe that, as cloning techniques continue to improve, we will be able to maintain any infertile lines of both males and females by using their somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cloned embryos of both inbred and outbred mice may reach term, but those that survive birth and beyond are very rare, with the exception of strain 129 (12,13). We found that ntES cell lines were readily established from cloned blastocysts not only of hybrid mice but also of outbred (ICR) and inbred mice (18,28) (Table 2). This raises the question of how ntES cell lines are established from cloned embryos that are otherwise destined to die (34).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, aged oocytes are likely to display a corresponding increase in the proportion of non-viable embryos following fertilization as a result of chromosomal abnormalities. Post-ovulatory aged oocytes purportedly exhibit significantly higher instances of chromosome misalignment, potentially as a consequence of meiotic spindles that are elongated, dispersed or disrupted (Wakayama et al 2004). These characteristics increase the likelihood for erroneous chromosome separation and hence aneuploidy (Mailhes et al 1998).…”
Section: Poor Embryo Qualitymentioning
confidence: 99%
“…Post-ovulatory aged oocytes exhibit numerous aberrations in their cell biology including partial cortical granule exocytosis (Szollosi 1971, Dodson et al 1989, Ducibella et al 1990, Xu et al 1997, zona hardening (Longo 1981, Dodson et al 1989, Xu et al 1997, a decrease in critical cell cycle factors including maturation-promoting factor (MPF) and MAPK (Kikuchi et al 2002), mitochondrial dysfunction (Chi et al 1988, Takahashi et al 2003, Tatone et al 2011, Zhang et al 2011, Lord et al 2013, spindle abnormalities (Wakayama et al 2004), losses of chromosomal integrity (Spielmann et al 1985, Mailhes et al 1998, Wakayama et al 2004) and epigenetic changes (Liang et al 2008; Table 1). Not surprisingly, the process of post-ovulatory ageing culminates in apoptosis (Fujino et al 1996) as a result of decreases in expression of the anti-apoptotic protein BCL2 (Gordo et al 2002, Ma et al 2005) and the activation of caspases (Takai et al 2007, Lord et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…También se confirma en dos revisiones sistemáticas el mayor riesgo que tienen los niños ART de presentar más mortalidad perinatal, ser de pretérmino, de menor peso, de ser pequeños para la edad gestacional, de nacer más por cesárea y de necesitar más tratamientos en unidades de cuidados intensivos neonatales 15,27,28 . Respecto a la vitalidad y capacidad de desarrollo de los ovocitos de animales, guardados a temperatura ordinaria o refrigerados, se encuentra que hay deterioro con el tiempo especialmente en aquellos guardados a temperatura ambiente 29 .…”
Section: Confirmación De Los Riesgos De Artunclassified